Contemporary predictors of death and sustained ventricular tachycardia in patients with repaired tetralogy of Fallot enrolled in the INDICATOR cohort - Valente, Anne Marie; Gauvreau, Kimberlee; Assenza, Gabriele Egidy; Babu-Narayan, Sonya V; Schreier, Jenna; Gatzoulis, Michael A; Groenink, Maarten; Inuzuka, Ryo; Kilner, Philip J; Koyak, Zeliha; Landzberg, Michael J; Mulder, Barbara; et al. (Heart (British Cardiac Society), 2014)
Objective Patients with repaired tetralogy of Fallot (TOF) experience increased rates of mortality and morbidity in adulthood. This study was designed to identify risk factors for death and ventricular tachycardia (VT) in a large contemporary cohort of patients with repaired TOF. Methods Subjects with repaired TOF from four large congenital heart centres in the USA, Canada and Europe were enrolled. Clinical, ECG, exercise, cardiac magnetic resonance (CMR) and outcome data were analysed. Results Of the 873 patients (median age 24.4 years), 32 (3.7%) reached the primary outcome (28 deaths, 4 sustained VT; median age at outcome 38 years; median time from CMR to outcome 1.9 years). Cox proportional-hazards regression identified RV mass-to-volume ratio ≥0.3 g/mL (HR, 5.04; 95% CI 2.3 to 11.0; p<0.001), LV EF z score<−2.0 (HR, 3.34; 95% CI 1.59 to 7.01; p=0.001), and history of atrial tachyarrhythmia (HR, 3.65; 95% CI 1.75 to 7.62; p=0.001) as outcome predictors. RV dysfunction was predictive of the outcome similar to LV dysfunction. In subgroup analysis of 315 subjects with echocardiographic assessment of RV systolic pressure, higher pressure (HR 1.39; 95% CI 1.19 to 1.62; p<0.001) was associated with death and sustained VT independent of RV hypertrophy and LV dysfunction. Conclusions RV hypertrophy, ventricular dysfunction and atrial tachyarrhythmias are predictive of death and sustained VT in adults with repaired TOF. These findings may inform risk stratification and the design of future therapeutic trials.